Understanding Social and Environmental Hazards in Urban Areas: An Analysis from Barranquilla, Colombia - Marina B. Martínez-González (MDPI AG, 2021)
The present research aims to understand the challenges faced by a Colombian city in the context of multidimensional risk scenarios, given the existing demographic and socio-economic conditions and local perspectives and perceptions regarding socio-environmental risks. The research was undertaken in the city of Barranquilla, northern Colombia. A survey was designed to analyze (1) the general socio-economic and vulnerability conditions of a communities’ sample, (2) information related to hazards and disaster risk in their neighbourhoods, and (3) information on actions to mitigate risk. Three hundred and ninety-one people were surveyed. Likert scale and Pearson's Chi-square test and descriptive, inferential statistical methods, regression models, and the Mann–Whitney U test were used to process the results. Respondents lived, in general, under precarious socio-economic conditions (such as low income or lack of infrastructure and others). Given socio-environmental constraints, the research revealed that hazards such as urban stream flooding and robbery were the most negatively associated with the respondent’s quality of life. Regarding the actions to avoid losses, 84% of respondents had not implemented any preventive action. Respondents also have low awareness of the need to implement risk prevention actions. Social risks and the configuration of anthropic hazards stand out as principal centres for concern.